2022
DOI: 10.1103/physrevb.106.094418
|View full text |Cite
|
Sign up to set email alerts
|

Particle-like skyrmions interacting with a funnel obstacle

Abstract: The skyrmion-substrate interaction is an important issue to consider when studying particle-like skyrmions in nanostructures, which may strongly affect the skyrmion dynamics and lead to complex dynamic phenomena. Here, we report the current-driven dynamic behaviors of particle-like skyrmions interacting with the funnel obstacle in a ferromagnetic layer. We computationally demonstrate that a funnel obstacle with enhanced perpendicular magnetic anisotropy can be used to modify the dynamics of skyrmions due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The steady speed v ts can be derived by solving eqn (5a) as follows: 20,37 v ts E p 2 uD sk /(aD) (6) where D C 2p(R sk /D + D/R sk ), and it is roughly equal to 4p. Then, the frequency f can be given by…”
Section: Skyrmion Dynamics In a Standard Nanodiskmentioning
confidence: 99%
See 1 more Smart Citation
“…The steady speed v ts can be derived by solving eqn (5a) as follows: 20,37 v ts E p 2 uD sk /(aD) (6) where D C 2p(R sk /D + D/R sk ), and it is roughly equal to 4p. Then, the frequency f can be given by…”
Section: Skyrmion Dynamics In a Standard Nanodiskmentioning
confidence: 99%
“…Magnetic skyrmion, 1-3 a particle-like spin structure usually stabilized by Dzyaloshinskii-Moriya (DM) interaction, 4,5 has attracted much interest because of its rich physics [6][7][8] and possible implementations in various devices such as skyrmion diodes, 9,10 skyrmion ratchets, 11 racetrack memories, 12 logic gates, [13][14][15][16] and nano-oscillators. [17][18][19][20][21][22][23][24][25][26][27][28] Among them, nanooscillators based on skyrmions in circular nanodisks have been heavily studied because their high-frequency motion can be easily used for microwave generators and/or detectors.…”
Section: Introductionmentioning
confidence: 99%
“…However, skyrmions could be destroyed by touching the edge. Recently, it has been shown that a more effective strategy to confine, protect, and control skyrmions in magnetic thin films is to construct defect lines with different magnetic properties [63][64][65][66][67][68][69][70][71][72][73][74] , which can be realized in engineered multilayer nanostructures 75) or by using focused irradiation 76) . However, the helicity dynamics of a frustrated skyrmion confined by defect lines have not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The square pattern is made of four obstacle bars, which are rectangle regions locally modified to have enhanced PMA K 0 . We assume that K 0 / K = 10 in order to make sure that the skyrmions cannot penetrate the obstacle boundary . Such a square pattern on the ferromagnetic substrate can, in principle, be fabricated in experiments. , The width of each obstacle bar is 10 nm, and the distance between two parallel inner edges of the square pattern is 100 nm.…”
mentioning
confidence: 99%